IMPLEMENTATION OF THE ‘PELAKU PARADEWI’ WEBSITE TO IMPROVE THE EFFICIENCY OF POPULATION ADMINISTRATIVE SERVICES IN BANGUN VILLAGE, MOJOKERTO REGENCY - Purwanto, Ferisha Ainurrahmasari; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research looks into the rollout of the Pelaku ParaDewi website, a digital advancement launched by the Mojokerto Regency Government aimed at enhancing population administrative services at the village level. Method: A descriptive qualitative method was employed for data gathering through interviews, observations, and documentation in Bangun Village. Result: The results indicate that Pelaku ParaDewi speeds up the processing of essential population documents like Identity Cards, Family Cards, and birth or death certificates by decreasing the dependence on traditional procedures at the regency office. This system improves efficiency for village officials, lessens travel expenses for residents, and boosts service responsiveness. Analyzing the situation through the Technology Acceptance Model (TAM) shows that the adoption of the system is greatly impacted by its perceived usefulness and ease of use, while the e-government readiness perspective indicates adequate infrastructure, human resources, and institutional backing. Novelty: Although there are technical hurdles and a limited range of services, Pelaku ParaDewi shows considerable promise as a model that can be replicated for inclusive and sustainable digital public service innovation in rural Indonesia.